2020
DOI: 10.1371/journal.pone.0229169
|View full text |Cite
|
Sign up to set email alerts
|

Verbing nouns and nouning verbs: Using a balanced design provides ERP evidence against “syntax-first” approaches to sentence processing

Abstract: In this event-related potential (ERP) study we reevaluate syntax-first approaches to sentence processing by implementing a novel paradigm in French that includes correct sentences, pure syntactic category violations, lexical-semantic anomalies, and combined anomalies. Our balanced design systematically controlled for target word (noun vs. verb) and the context immediately preceding it. Group results from 36 native speakers of Quebec French revealed that, up to 300 ms, ERPs elicited by syntactic category violat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 72 publications
2
11
0
Order By: Relevance
“…In terms of amplitude modulations, both of the incongruous and ungrammatical conditions (repetition and non-repetition) elicit central-parietal P600 effects. The results agree with several previous studies (e.g., Ye et al, 2006;Zhang et al, 2013;Yang et al, 2015;Fromont et al, 2020). Although there is a difference in terms of memory retrieval facilitation between repetition and non-repetition conditions, the amplitudes of P600s in these two anomalous conditions were not statistically different from each other (based on an overall averaged data comparison from 500 to 800 ms time window).…”
Section: Discussionsupporting
confidence: 92%
“…In terms of amplitude modulations, both of the incongruous and ungrammatical conditions (repetition and non-repetition) elicit central-parietal P600 effects. The results agree with several previous studies (e.g., Ye et al, 2006;Zhang et al, 2013;Yang et al, 2015;Fromont et al, 2020). Although there is a difference in terms of memory retrieval facilitation between repetition and non-repetition conditions, the amplitudes of P600s in these two anomalous conditions were not statistically different from each other (based on an overall averaged data comparison from 500 to 800 ms time window).…”
Section: Discussionsupporting
confidence: 92%
“…A main Unmasked Correctness effect arose at around 910 ms with a widespread central negativity, which might reflect a N400 component to morphosyntactic anomalies (for similar N400 topographies and functional significance see: Molinaro et al, 2015;Fromont et al, 2020;Jiménez-Ortega et al, 2020). However, the onset of the component seems to be somehow delayed in comparison to other recent studies using similar sentences (Hinchcliffe et al, 2020;Jiménez-Ortega et al, 2020), wherein LAN/N400 components to syntactic anomalies are generally triggered at around 400 ms.…”
Section: The Flexible and Content-dependent Nature Of Syntaxmentioning
confidence: 59%
“…Instead, the N400 would be an indication of difficulties with word retrieval (e.g. Choudhary et al, 2009 ; Brouwer et al, 2017 ) in the cases where the presented word is not an expected verb (see Fromont et al, 2020 for a biphasic N400/P600 response to word category violations).…”
Section: Current Studymentioning
confidence: 99%
“…In a recent paper, Fromont et al (2020) have also suggested that a biphasic N400-P600 response can be considered to be an index of word order violations (referred to as a syntactic category violation in the paper). When controlling for the word preceding the critical word (e.g.…”
Section: Introductionmentioning
confidence: 99%